2011
DOI: 10.1007/s10585-011-9400-1
|View full text |Cite
|
Sign up to set email alerts
|

Dairy milk fat augments paclitaxel therapy to suppress tumour metastasis in mice, and protects against the side-effects of chemotherapy

Abstract: Milk fat is a natural product containing essential nutrients as well as fatty acids and other food factors with reported anti-cancer potential. Here bovine milk fat was tested for its ability to inhibit the growth of breast and colon cancers and their metastasis to the lung and liver; either alone or in combination with the chemotherapeutic agent paclitaxel. A diet containing 5% typical anhydrous milk fat (representing ~70% of the total dietary fat component) fed to Balb/c mice delayed the appearance of subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…7 The combination of different drugs provides several advantages such as synergistic effects and reversal of drug resistance. 7,11,12 Combined treatment with combretastatin and the apoptosis-inducing agent doxorubicin was more effective at suppressing the growth of melanoma and lung carcinoma than treatment with either of these agents alone. 13 GEM is used extensively in combination with other chemotherapeutic drugs for the treatment of recurrent ovarian cancers and small cell lung cancers.…”
Section: Introductionmentioning
confidence: 99%
“…7 The combination of different drugs provides several advantages such as synergistic effects and reversal of drug resistance. 7,11,12 Combined treatment with combretastatin and the apoptosis-inducing agent doxorubicin was more effective at suppressing the growth of melanoma and lung carcinoma than treatment with either of these agents alone. 13 GEM is used extensively in combination with other chemotherapeutic drugs for the treatment of recurrent ovarian cancers and small cell lung cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that chemotherapeutic drugs cannot successfully treat cancer as they have severe side effects including various types of rash, hair loss, painful paronychia and xerosis cutis (18). Plants as medicinal agents have been used in the treatment of various types of diseases in humans (19)(20)(21)(22)(23) and a number of investigators have also reported that natural products may be safe and free from side effects (24)(25)(26)(27). Particularly, PML as a natural product, has been reported to exert its anticancer effect via DNA damage in cancer cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Products were manufactured in a facility accredited by the Ministry for Primary Industries with an approved Hazard Analysis and Critical Control Point plan. They were administered orally as one 100-g serving of ice cream daily for 10-18 days pre-chemotherapy (for priming the gut [5,6]) and continued for 6 weeks from the start of chemotherapy (a total of 8 weeks±4 days). Randomisation was stratified and blocked by length of planned chemotherapy cycle (2 vs 3 weeks) and study site using random block sizes of 4 or 6.…”
Section: Methodsmentioning
confidence: 99%
“…AMF is a commercial food product that has been widely used in the food industry for many years. Animal data have shown that both iron-saturated lactoferrin and milk fat prevent chemotherapy-induced gut damage and aid recovery from neutropenia [5][6][7] and that the two components work synergistically (unpublished results). There have been over 20 studies in humans investigating lactoferrin's effect on iron absorption [8], Helicobacter pylori eradication [9], hepatitis C eradication [10], a variety of other infections [11], colonic polyps [12] and modulation of tumour growth [13], including two short-term trials involving high doses of fully iron-saturated lactoferrin [8,14].…”
Section: Introductionmentioning
confidence: 94%